2021
DOI: 10.1016/j.apsb.2021.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Gains from no real PAINS: Where ‘Fair Trial Strategy’ stands in the development of multi-target ligands

Abstract: Compounds that selectively modulate multiple targets can provide clinical benefits and are an alternative to traditional highly selective agents for unique targets. High-throughput screening (HTS) for multitarget-directed ligands (MTDLs) using approved drugs, and fragment-based drug design has become a regular strategy to achieve an ideal multitarget combination. However, the unexpected presence of pan-assay interference compounds (PAINS) suspects in the development of MTDLs frequently results in nonspecific i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 112 publications
(250 reference statements)
0
15
0
Order By: Relevance
“…Since the publications regarding PAINS, by Baell and Holloway [97], and colloidal aggregators, by McGovern et al, which revealed that some substructures are often frequent hitters or promiscuous inhibitors [98], based on high-throughput screening assays, increased awareness of these categories of compounds have become important during drug discovery. However, several publications have argued that not all frequent hitters should be randomly discarded without first validating whether they are target-specific or truly promiscuous [58,[99][100][101][102]. In a recent editorial, Bajorath mentioned that the chemical integrity and specific biological activity of compounds containing PAINS substructures should be considered in the context of the whole compound and how they are embedded in the structure.…”
Section: Discussionmentioning
confidence: 99%
“…Since the publications regarding PAINS, by Baell and Holloway [97], and colloidal aggregators, by McGovern et al, which revealed that some substructures are often frequent hitters or promiscuous inhibitors [98], based on high-throughput screening assays, increased awareness of these categories of compounds have become important during drug discovery. However, several publications have argued that not all frequent hitters should be randomly discarded without first validating whether they are target-specific or truly promiscuous [58,[99][100][101][102]. In a recent editorial, Bajorath mentioned that the chemical integrity and specific biological activity of compounds containing PAINS substructures should be considered in the context of the whole compound and how they are embedded in the structure.…”
Section: Discussionmentioning
confidence: 99%
“…McGovern et al as frequent hitters or promiscuous inhibitors 68 in high throughput screening (HTS) campaign, the awareness of these categories of compounds became part of the equation in drug discovery. However, several publications made counter-arguments that all frequent hitters should not be randomly discarded without validating whether they are target-specific or true promiscuous 43,[69][70][71][72] . In a recent Editorial, Bajorath mentioned that the chemical integrity and specific biological activity of compounds containing PAINS substructure should be considered in the context of the whole compounds and how they are embedded in the structure.…”
Section: And Colloidal Aggregators Bymentioning
confidence: 99%
“…Thiopyrano [2,3-d]thiazole derivatives are attractive objects in modern medicinal chemistry and possess a wide range of valuable biological activities, such as anticancer [1], antimicrobial [2], antiviral [3], and antifungal [4]. A retrosynthetic approach to thiopyrano [2,3d]thiazoles leads to 5-ene-4-thiazolidinones, which contain enone fragments in their structures and in this regard are characterized as PAINs with low selectivity and high reactivity toward the nucleophilic centers of biological molecules [5,6] (Figure 1). Application of the hetero-Diels-Alder reaction is a useful synthetic tool for the transformation of the 5-ene-4-thiazolidinones to the respective thiopyrano [2,3-d]thiazoles, which enables retaining or improving the pharmacological properties and removing the PAIN features from the molecules.…”
Section: Introductionmentioning
confidence: 99%
“…H NMR (500 MHz, DMSO-d 6 , δ): 1.92 (t, J = 6.0 Hz, 3H, CH 3 ), 3.27 (dd, J = 17.8, 3.9 Hz, 1H, CH 2 ), 3.71 (s, 3H, OCH 3 ), 3.93 (dd, J = 17.8, 11.8 Hz, 1H, CH 2 ), 5.61 (dd, J = 11.8, 3.9 Hz, 1H, CH 2 ), 6,79 (sext, J = 6.9 Hz, 1H, =CH),6.88 (d, J = 8.5 Hz, 2H, arom. ), 7.06 (d, J = 15.4 Hz, 1H, =CH), 7.13 (d, J = 8.5 Hz, 2H, arom.…”
mentioning
confidence: 99%